Pengaruh Work-Life Balance, Perceived Organizational Support, dan Working Time terhadap Job Hopping Generasi Z di Semarang - Permadani, Etika Wahyu; Sartika, Mila; Purwatiningsih, Aris Puji; Perdana, Tito Aditya (Jurnal EMT KITA, 2026)
The phenomenon of job hopping is becoming increasingly common among employees, particularly among Generation Z, who tend to switch jobs more readily when their work and personal life needs are not met. Therefore, this study aims to analyze the influence of Perceived Organizational Support, Work-Life Balance, and Working Time on job-hopping behavior. This study employs a quantitative approach with a causal design to test the relationships among variables. Data analysis was conducted using the Partial Least Squares (PLS) method via SmartPLS software, which involves two evaluation stages: the outer model to test the validity and reliability of the instruments, and the inner model to test the relationships among variables and test the hypotheses. The results indicate that, partially, Perceived Organizational Support and Work-Life Balance have a negative and significant effect on Job Hopping, meaning that the higher the organizational support and the better the work-life balance, the lower the tendency for employees to change jobs. Conversely, Working Time has a positive and significant effect on Job Hopping, indicating that long or suboptimal working hours increase employees’ tendency to change jobs. These findings provide practical implications for organizations to enhance organizational support and foster better work-life balance to reduce employee job-hopping rates.